Unveiling the glymphatic system’s impact on neurodegenerative diseases: a comprehensive bibliometric analysis (2012–2024) - Wang, Younian; Liu, Qiangsheng; Wu, Junyi; Meng, Kun; Zhou, Lanting; Ye, Fan (Frontiers in Aging Neuroscience, 2025)
BackgroundThe glymphatic system is a crucial factor in the development of neurodegenerative diseases (NDs) and holds substantial promise for therapeutic strategies. However, despite its growing significance, detailed bibliometric investigations specifically targeting the interplay between the glymphatic system and NDs are still sparse. This study pioneers a comprehensive bibliometric analysis to delineate the intellectual framework and emerging trajectories in glymphatic system research associated with NDs.Materials and methodsWe conducted an exhaustive search of the literature on the glymphatic system and NDs using the Web of Science Core Collection (WoSCC), Scopus, and Pubmed Central (PMC) databases. VOSviewer was applied for bibliometric analysis and visualization to scrutinize geographical distribution, institutional distribution, inter-journal connections, and keyword prevalence. Additionally, CiteSpace was utilized to intuitively explore and analyze journal interactions and citation dynamics. The bibliometrix R package was employed to construct visualized networks of international collaborations, as well as the relationships among authors, keywords, and journals. Data visualization was further enhanced with the aid of the WPS Office.ResultsA total of 865 relevant publications were retrieved, covering 92 countries, 1,471 research institutions, and 367 academic journals. Over the past thirteen years, both the number of publications and citations related to the glymphatic system in NDs have shown a significant upward trend, with neuroscience being the primary research field. Chinese authors over the world published the largest number of articles, while China and United States rank the highest in terms of publication and citation counts, also both demonstrate extensive international collaboration. And the Frontiers series journal publishes the most papers in this field, while Brain is the most frequently cited journal. The University of Rochester is the top-producing institution with an internally well-known Chinese research group. Keyword analysis highlights the glymphatic system, Alzheimer’s disease (AD), cerebrospinal fluid, and aquaporin 4 (AQP4) as core topics, with AQP4 polarization identified as a key regulatory factor for metabolic waste clearance. The main NDs under investigation are AD and Parkinson’s disease (PD).ConclusionThis study offers a comprehensive preliminary dissection of the research landscape, identifying current focal points and potential future directions in glymphatic system research related to NDs. By leveraging multiple bibliometric approaches, this study provides valuable insights into this burgeoning field.